Acceptance of donor breastmilk by mothers in Lagos: a cross-sectional survey - Olanike Olutekunbi; Olufunmilayo Opeyemi Oluwabiyi; Adegbajo Adedeji Odedina; Adaobi Uzoamaka Solarin; Ibironke Jadesola Akinola; Funlola Olusola Showunmi; Tolulope Adedoyin Olatunji; Gbenga Fakunle Abe; Oyejoke Oyapero; Grace Abosede Ogunleye; Opeyemi Oshinowo; Esther Olutola; et al. (International Journal Of Community Medicine And Public Health, 2026)
Background: Human breast milk meets the nutritional needs of babies and reduces the incidence of infection. Not all babies benefit from this nature’s gift. WHO recommends that such babies should receive the next preferred choice of donor breast milk (DBM), which is not common in Nigeria. This study aimed to determine the acceptance of donor breast milk by the mothers in Lagos State, South-Western Nigeria. Methods: A questionnaire-based, descriptive, cross-sectional study. Questionnaires were administered to mothers of babies attending the immunization and neonatal clinics at seven Lagos State government-owned hospitals from September to November 2021. Results: A total of 1750 questionnaires were analyzed. The mean age of the respondents was 30.9±6.3 years. Most respondents (59.2%) had a tertiary education. Most (88.8%) had no prior knowledge of DBM, and 83.5% would not allow their babies to receive DBM. Maternal education (p=0.031) and the mode of delivery (p=0.049) are significantly associated with the knowledge of DBM, and a significant association exists between knowledge of DBM and perception of receiving DBM (p=0.001). All mothers who had heard of DBM (100%) were willing to allow their babies to receive DBM, compared to only 5.9% of mothers who had not heard of DBM. Conclusions: Mothers in Lagos are not willing to give their babies DBM. Religious and cultural reasons strongly influence acceptance of DBM. These mothers, however, are willing to donate their milk for other babies.